Teaching Writing in Vietnam's Secondary and High Schools - Vu Phi Ho Pham; Minh Hoa Truong (MDPI AG, 2021)
The current study adopted features of a survey research design to examine the EFL high school teachers' beliefs about writing and its teaching, their actual classroom practices, and the interplays between their beliefs and practices in the realm of EFL writing instruction. A sample of seventy-six EFL teachers from the eight selected high schools situated in Ho Chi Minh City was recruited for the current survey. The beliefs and practices of EFL writing instruction of these studied teachers were elicited through a thirty-nine-item questionnaire, which was qualitatively analyzed by SPSS 20.0. The study results showed that most of the participants held different views/orientations about writing skills and teaching writing, consisting of form-based, cognitive process-based, functional social-based, and interactive social-based views; nevertheless, the form-based orientation was still most dominant in their beliefs. On the contrary, in practice, most high school teachers followed the product approach, which underlies form-based orientation in lieu of different approaches, explicitly interpreting the writing section's low results in the Vietnamese National GCSE examination in recent years.